Lack of diet segregation during breeding by male and female Northern Flickers foraging on ants. Issue 3 (23rd August 2013) - Gow, Elizabeth A.; Wiebe, Karen L.; Higgins, Robert J.
ABSTRACT: Sexual size dimorphism can result in reduced competition if it leads males and females to use different foraging techniques or consume different prey items. Among woodpeckers, differences between males and females in bill length are common and may explain foraging differences in this family of birds. Northern Flickers ( Colaptes auratus ) are ground‐foraging woodpeckers that specialize on ants. However, the overall contribution of ants to their diet and the proportions of particular ant genera in their diet are not well known. To understand the relationship between bill morphology and the consumption of prey items, we compared the bill length and bill width of male and female flickers. We then collected and analyzed fecal samples from breeding flickers ( N = 40 males, 33 females) at a study site in central British Columbia, Canada. Bills of male flickers were significantly longer (4%) and wider (5%) than those of females. Of 11 prey types identified, ants made up over 99% of their diet, and the abundance and composition of ant taxa in the diet did not differ between the sexes. We found significant year and time of season effects, with the abundance of Tapinoma sessile and Lasius spp. increasing from May to the end of June and differing between years. This difference in diet composition between years may have been due to changes in the abundance or accessibility of certain ant taxa related to differences in vegetation structure or weather. Nine ant taxa were consumed by flickers and the four most common were T. sessile, Lasius spp., Myrmica spp., and the Formica fusca species group. The degree of dimorphism in bill size of male and female Northern Flickers in our study was smaller than reported for several species of arboreal‐foraging woodpeckers, suggesting that bill size of ground‐foraging woodpeckers may not be strongly linked to niche separation at the level of prey selection.